Effects of Biogas Slurry on Microbial Phosphorus Metabolism in Soil of Camellia oleifera Plantations - Quanxun Chen; Jianbo Cheng; Guangliang Tian; Tengbin He; Hu Wang; Tao Zhang; Jianming Hong; Liangyu Dai; Tianling Fu (Land)
The use of biogas slurry as an alternative to chemical fertilizers for supplying phosphorus to plants is gaining increasing attention. However, the mechanisms by which biogas slurry activates soil phosphorus and influences phosphorus-metabolizing microorganisms are not yet fully understood. This study characterized the effects of controlled biogas slurry application gradients (0, 13, 27, 40, and 53) on the soil phosphorus structure, camellia oleifera (CO) phosphorus content, microbial phosphorus metabolism functional gene abundance, and phosphorus transformation functions in CO plantation soils. Increasing the dosage of biogas slurry effectively enhanced soil phosphorus levels and significantly increased the proportions of aluminum-bound phosphorus (Al-P) and iron-bound phosphorus (Fe-P). Under simulated conditions, the contents of soil Al-P, Fe-P, and organic phosphorus significantly decreased and transformed into occluded phosphorus (O-P) and calcium-bound phosphorus (Ca-P), while under field conditions, due to spatial heterogeneity, the changes in soil phosphorus and its forms were not distinctly evident. The application of biogas slurry did not significantly alter the major phyla of phosphorus-metabolizing microorganisms in the soil, but significant changes in the abundance of different microorganisms were observed. The abundance of dominant bacterial communities such as Chloroflexi_bacterium increased, while the abundance of communities such as Actinomycetia_bacterium decreased. By influencing the expression of soil microbial functional genes related to inorganic phosphorus solubilization, organic phosphorus mineralization, phosphorus deficiency response regulation, and phosphorus transport, the solubility of inorganic phosphorus and the mineralization rate of organic phosphorus in the soil were enhanced. Additionally, it may weaken microbial phosphorus uptake by inhibiting intercellular phosphorus transport in microorganisms, thereby improving the utilization of soil phosphorus by CO.